2007
DOI: 10.1063/1.2776252
|View full text |Cite
|
Sign up to set email alerts
|

Influence of traps on top and bottom contact field-effect transistors based on modified poly(phenylene-vinylene)

Abstract: We report on the investigations of the differences in the measured current characteristics of source/drain top contact (TOC) and bottom contact (BOC) organic field-effect transistors (OFETs). The active layer was made from poly[1,4-phenylene-(4-methylphenyl)imino-4,48-diphenylene-(4-methylphenyl)imino-1,4-phenylenevinylene-2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene-vinylene] and a highly doped silicon wafer with a thermal oxide was used for the gate and the insulator, respectively. Both transistors show a goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In particular, we used exponential distributions of donor-like (located in the lower half of the bandgap) and acceptor-like (located in the upper half of the bandgap) states. Concerning the mobility model, we adopted in our simulations a constant carrier band mobility, as already in our previous works [15,21,22] and also assumed in other works [12,14]. The adopted model can be assimilated to the multiple trapping and release (MTR) model [23], where transport occurs via extended states, a widely accepted model for high field effect mobility devices [24].…”
Section: Numerical Simulationsmentioning
confidence: 98%
See 2 more Smart Citations
“…In particular, we used exponential distributions of donor-like (located in the lower half of the bandgap) and acceptor-like (located in the upper half of the bandgap) states. Concerning the mobility model, we adopted in our simulations a constant carrier band mobility, as already in our previous works [15,21,22] and also assumed in other works [12,14]. The adopted model can be assimilated to the multiple trapping and release (MTR) model [23], where transport occurs via extended states, a widely accepted model for high field effect mobility devices [24].…”
Section: Numerical Simulationsmentioning
confidence: 98%
“…In particular, the presence of Schottky barriers [11,[13][14][15][16][17], trap state density [12] and field dependence of carrier mobility [11,13] have been shown to influence the contact characteristics. Recent works have also shown that barrier lowering, induced by image force (Schottky effect) [15,16], as well as other field dependent mechanisms [15], can play an important role, determining a substantial enhancement in the carrier injection from the edge of the source contact, where the electric fields are more intense [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms have been discussed in literature to understand such a non‐linearity, which primarily can be observed in staggered bottom gate devices . The proposed explanations include: i) the anisotropy of the charge carrier mobility for thick semiconductor films, ii) common gate‐induced parasitic currents that hinder the accumulation of the mobile charges by forming an effective potential barrier under the drain contact, and iii) large barrier heights at the injecting electrode stemming from an energy misalignment between the work functions of contact material and semiconductor . Since neither thick semiconductor films, nor a common gate or large contact barriers are found in our devices, none of these mechanisms seem applicable here.…”
Section: Capacitance and Extracted Transistor Parameters For Al2o3 + mentioning
confidence: 99%
“…On the other hand, scaling down the transistor channel length to L = 10 m, the normalized drain current shows substantial departure from the expected behavior. We have also tested the applicability of gradual channel approximation (GCA) to device characteristics by comparing the measured output characteristics of the devices with different channel lengths, using with the following equation: ∫ [13] where G(V)= I d (V gs )/V ds is the channel conductance determined by the long channel transfer characteristics measured at low V ds (0.1V).…”
Section: Contact Resistance In Staggered Printed Otftsmentioning
confidence: 99%